THE EFFICACY OF HIGH-DOSE SIMVASTATIN IN ACUTE PERIOD OF ISCHEMIC STROKE - V. V. Yakusevich; A. Yu. Malygin; S. V. Lychenko; A. S. Petrochenko; A. V. Kabanov (Столичная издательская компания, 2015)
Aim. To estimate in a 12-month study mortality and frequency of recurrent cardiovascular events, dynamics of neurological deficit and endothelial dysfunction in patients with the first-time ischemic stroke treated with simvastatin 40 mg/day in acute period of the disease. Materials and methods. The efficacy of high-dose simvastatin (40 mg/day) therapy initiated in acute stage of ischemic stroke was evaluated in 12-month comparative randomized study. Patients of the first group (n=97) received standard stroke therapy , and patients of the second group (n=86) also received standard treatment and simvastatin additionally. Combined endpoint (cardiovascular death + recurrent cardiovascular events + necessity of readmission), dynamics of neurological status and endothelial function were considered.  Results. Primary combined endpoint was achieved in 66 cases in the first group (68.04%) and in 47 (54.65%) in the second one (p=0.043). Neurological status evaluated by National Institutes of Health Stroke Scale (NIHSS), Mini-Mental State Examination (MMSE) scale, and Scandinavian scales had a faster positive dynamics in patients receiving simvastatin. The same patients revealed more intense and quick decrease in desquamated plasma endotheliocytes. Conclusion. Simvastatin 40 mg/day prescribed along with neuroprotective and antihypertensive treatment in acute stage of ischemic stroke leads to lowering of recurrent cardiovascular events number, positive dynamics of neurological status, regression of endothelial dysfunction reflected by significant decrease in number of circulating desquamated endotheliocytes.